FORMULATION AND EVALUATION OF GEL LOADED WITH MICROSPHERES OF APREMILAST FOR TRANSDERMAL DELIVERY SYSTEM - PRIYANKA, N. V. SAI; NEERAJA, P.; MANGILAL, T.; KUMAR, M. RAVI (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The main objective of the present research work was to formulate and evaluate gel loaded with microspheres of apremilast to increase bioavailability and to reduce the dosing frequency and to improve patient compliance. Methods: Gel loaded with microspheres of apremilast was prepared by solvent evaporation method by taking different ratios of polymers. Ethyl cellulose as a polymer, dichloromethane solvent is used as drug solubility, polyvinyl alcohol as a surfactant, and sodium alginate is used as gelling agent. Prepared gel loaded with microspheres was evaluated for drug interactions by Fourier transform infrared (FTIR), differential scanning calorimetry studies, and surface morphology by scanning electron microscopy (SEM), to select effective one among all formulations. The prepared formulations (F1–F6) were evaluated for pre-formulation studies, spreadability, viscosity, pH measurement, gel strength, homogeneity, drug content, in vitro diffusion studies, drug kinetics, and finally for stability studies. Results: Differential scanning calorimeter studies confirmed that there is no drug interaction between drug and excipients. FTIR spectroscopy studies confirmed that there is compatibility between drug and excipients. Regular and spherical shape particles with smooth surface were observed in the SEM photographs. The optimized gel loaded with microspheres of F4 formulation (drug: polymer in 1:4 ratio) is more effective compared to all formulations. The prepared gel showed acceptable physical properties such as spreadability (5.86±0.54 g.cm/s), viscosity (568 cps), pH (6.33±0.55), gel strength (38 s) and drug content (90.00±0.71%). In vitro diffusion studies have shown 80.1±1.92% drug release in 10 h. Drug kinetics follows zero order kinetics and n value was found to be 0.721. Stability studies were done for 3 months. Conclusion: All the results show that the gel loaded with microspheres of apremilast can be effectively used for the treatment of psoriasis and psoriatic arthritis.